MENGOPTIMALKAN PEMBELAJARAN SENI RUPA DI SEKOLAH DASAR : STRATEGI DAN PRAKTEK TERBAIK - Yulia Marni; Desyandri; Farida Mayar (STKIP Subang, 2023)
The purpose of writing this article is to discuss strategies and best practices in optimizing visual arts learning in elementary schools. Fine arts have an important role in basic education, engaging students in creative expression, developing critical thinking, and increasing self-confidence. The main focus of this article is the use of art projects as an effective learning strategy. Art projects engage students in practical activities that allow them to learn thoroughly about art concepts and apply them in their own work. This article also describes the benefits of art projects in increasing student engagement, encouraging creative exploration, and strengthening interpersonal skills. The stages of implementing an art project are adapted to the developmental level of children, ensuring a suitable and interesting learning experience for them. In addition, this article outlines best practices in art learning, including creating a creative and inclusive classroom environment, encouraging students' exploration and self-expression, and providing constructive feedback and appreciation for their art. In facing challenges such as the integration of fine arts into a dense curriculum and the limited knowledge of art teachers, this article also provides solutions that can help maximize time and resources and improve teacher competence. It is hoped that this article can provide insight and practical guidance for the development of effective art learning in elementary schools.